Heritage Building Era Detection using CNN. (September 2019) - Samaun Hasan, Md.; Ali, Mohammad; Rahman, Mizanur; Arju, Hosne Ara; Alam, Mirza Mohtashim; Salah Uddin, Md.; Allayear, Shaikh Muhammad
Abstract: The Indian subcontinent is a southern area of Asia continent which includes India, Bangladesh, Pakistan, Nepal, Bhutan, Maldives, and Sri Lanka. In the different periods, different rulers had ruled in these territories such as the Sultanate period (1206–1526) and Mughal period (1526–1540, 1555–1857). In addition, various ancient and heritage structure patterns show the different historical and religious characteristics of the old civilizations. This research presents a computational method for identifying the construction period or era of old heritage building by using feature detection. We have done this experiment for the application aspect, where the tour guide is not available this application will help the tourists for knowing the construction period or era by detecting the features of old spectacular architecture. In this study, we have focused on the constructional characteristics of old architectural sites by using Canny Edge Detector method. After using the Canny Edge Detector method, we have categorized different types of features among the buildings such as Dome, Minaret or Tower, Ratna, and Front. The different eras old structure contains different characteristics of the Dome, Minaret or Tower, Ratna, and Front. Finally, we have developed a neural network based model which can identify the building's construction era of the Sultanate period and Mughal period.